Factors Related to Husband’s Companion in Childbirth on Penyengat Island - Rahmadona Rahmadona; Utami Dewi; Nurniati Tianastia Rullyni (Alliance oh Health Activists (AloHA), 2022)
More than 90% of maternal deaths are caused by complications that often occur during or around childbirth. Reducing the incidence of childbirth complications requires the family's participation, especially the husband. The presence of the husband as a birth attendant is essential because it can create a sense of security, and comfort, increase the mother's confidence, reduce anxiety about the delivery process, reduce the intensity of labor pain, reduce labor complications, and speed up the delivery process. This research aims to find out the factors related to the husband's assistance in the delivery process. This study was analytic observational with a cross-sectional approach. The study was conducted on Penyengat Island, Tanjungpinang City, Riau Islands Province, on 39 husbands of normal delivery mothers using questionnaires and observation sheets. The Chi-square statistical test with a significant degree of 95% (α 0.05) was used for data analysis. There is a significant relationship between knowledge (p = 0.027), attitude (p = 0.004) and motivation (p = 0.047) with husband's assistance in childbirth. There was no relationship between the factors of age (p = 0.555), occupation (p = 0.357) and education (p = 0.287) with husband's assistance in the delivery process. The study concludes that husbands can provide good delivery assistance if their knowledge, attitudes, and motivation are also good, regardless of their educational background, age, and occupation. It is recommended that special guidelines are needed to increase the husband's participation in childbirth assistance. Keywords: childbirth assistance; husband; knowledge; attitude; motivation; age; occupation; education